Christianity, Plasticity, and Spectral Heritages - Taylor, Victor E. (Radical Theologies and Philosophies, 2017)
This book is an interdisciplinary study of the cultural representations of Jesus in the context of contemporary religious theory and continental philosophy. It looks at Jesus in view of an updated Derridean hauntology and spectrality, with an emphasis on the inherent plasticity of the Christian heritage. While the work engages with the recent Jesus-centered writings of Slavoj Žižek, François Laruelle, and Giorgio Agamben, it places a greater and much needed emphasis on the philosophical, theological, and cultural links between a plastic, hauntological Christian heritage and Jesus’s historically evolving plural subjectivity, with the latter explored in texts of popular culture. It is a multidisciplinary study of Jesus, as well as a dynamic Christian heritage that simultaneously constructs and deconstructs Jesus’s philosophical, political, and cultural centrality